Maintaining One's Living Standard at Old Age: What Does that Mean? Evidence Using Panel Data from Germany - Christian Dudel; Notburga Ott; Martin Werding (Center for Economic Studies and ifo Institute (CESifo), 2013)
How much retirement income is needed in order to maintain one's living standard at old age? As it is difficult to find a firm basis for an empirical treatment of this question, we employ a novel approach to assessing an adequate replacement rate vis-à-vis income in the pre-retirement period. We subject indications regarding satisfaction with current income as collected in the German Socio-Economic Panel (GSOEP) to longitudinal analyses, using linear fixed-effects models and fixed-effects ordered logit models as our main analytical tools. We obtain a required net replacement rate of about 87% for the year of entry into retirement as a rather robust result, while replacement rates keeping the living standard unchanged may slightly decline over the retirement period.
Keywords: D10; D91; H55; J32; 330; retirement; living standard; replacement rate; pensions; saving; satisfaction